1967
DOI: 10.1037/h0082989
|View full text |Cite
|
Sign up to set email alerts
|

The effect of embryonic X-irradiation on the approach and following response in newly hatched chicks.

Abstract: Chicken embryos were treated with doses of 200r or 400r of X-irradiation at either Day 2 or Day 9 of embryonic development. The hatched chickens were first exposed to an imprinting stimulus at either 10 hr. or 100 hr. after hatching and their approach behaviour was compared to that of untreated controls. There were significant differences between the early and late imprinting groups. X-irradiation significantly lowered imprinting scores but only for those chicks treated on Day 9 of incubation and given early i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1968
1968
1989
1989

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…A scan over the embryological periods of skeletal formation and neural differentiation has shown that a radiosensitive period for the pecking response exists between Days 6 and 8 of incubation. This result agrees rather well with the outcome of earlier work (Strobel et al, 1967;Strobel et al, 1968) which suggested a similar increase in susceptibility to irradiation insult between Days 7 and 9 for the approach and following response in chicks. Variability was the main indicator and the effect appeared over the course of several trials.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A scan over the embryological periods of skeletal formation and neural differentiation has shown that a radiosensitive period for the pecking response exists between Days 6 and 8 of incubation. This result agrees rather well with the outcome of earlier work (Strobel et al, 1967;Strobel et al, 1968) which suggested a similar increase in susceptibility to irradiation insult between Days 7 and 9 for the approach and following response in chicks. Variability was the main indicator and the effect appeared over the course of several trials.…”
Section: Discussionsupporting
confidence: 92%
“…The same technique has been suggested to identify stages in embryological development when the neural components are formed that underlie stereotyped behavior patterns after birth (Furchtgott, 1963a). In a first attempt, the approach response in newly hatched chicks, elicited by retinal flicker (James, 1959), has been shown to be modified by X-radiation on Days 7-9 of incubation (Strobel, Baker, & Macdonald, 1967;Strobel, Clark, & Macdonald, 1968). Roughly the same period, Days 8-10, was identified by Karnofsky, Patterson, and Ridgeway (1950) as maximally radiosensitive when assessed by acute and delayed cell death.…”
mentioning
confidence: 99%
“…Different investigators have argued for the pivotal contribution of each of these physiological mechanisms, even with respect to the same class of sensitive period. For example, in imprinting among young precocial birds, Martin and Schutz (1974) determined that general arousal played a significant role; Strobel, Baker, and MacDonald (1967) and Bradley (1985) that change in central nervous system structures played a significant role; and Immelmann (1972) that advances in visual perceptual ability played a significant role.…”
Section: A Sensitive Period Framework: II Causal Interpretationsmentioning
confidence: 99%
“…This suggests that radiosensitive central nervous system structures important to imprinting are formed about day 9 in the chick embryo (Strobel et al, 1967). Brooks (1962) found no difference in the behavior of skinks irradiated prenatally or as adults from that of untreated skinks.…”
Section: Miscellaneous Studiesmentioning
confidence: 98%
“…Strobel et al (1967) found that embryonic x-ray treatment advanced the offset of the sensitive period for imprinting in chicks. This agrees with the general conclusions from other research that prenatally irradiated animals show increased fearfulness and the general view that the end of the sensitive period for imprinting comes with the onset of fear reactions in birds.…”
Section: Emotionalitymentioning
confidence: 99%